The effect of whole-body cryostimulation on lysosomal enzyme activity in kayakers during training - Wozniak, A.; Wozniak, B.; Drewa, G.; Mila-Kierzenkowska, C.; Rakowski, A. (European Journal of Applied Physiology, 2007)
Effects of whole-body cryostimulation on lysosomal enzyme activity: acid phosphatase (AcP), arylsulphatase (ASA) and cathepsin D (CTS D), as well as on the creatine kinase (CK), and the cortisol concentration in the serum of kayakers during training were studied. Additionally, the effect of a single cryostimulation treatment in untrained men was evaluated. The kayakers were subjected to a ten-day training cycle, in which training sessions were preceded by whole-body cryostimulation at a temperature ranging from -120 to -140°C, and to a control training without cryostimulation. Blood samples were taken from the kayakers before the training and after the sixth and tenth day of training and from untrained men before and after cryostimulation. The single cryostimulation caused a 30% (P < 0.05) decrease in the CK activity in untrained men. After the sixth day of training with cryostimulation, the activity of ASA was 46% (P < 0.001), AcP 32% (P < 0.05) and CK 34% lower (P < 0.05) than after the sixth day of training without cryostimulation. The results support that preceding training with whole-body cryostimulation alleviates exertion stress by a stabilisation of lysosomal membranes.